An investigation of dental luting cements - Black, Simon Mitchell (The University of Edinburgh, 1992)
The retentive power of selected dental luting cements has been investigated in-vitro with regard to the effects of taper, temporary cementation and recementation.

A standard test method has been developed from measurements of clinically observed tapers and cementation pressures achieved, and account has been taken of the dimensions of human teeth. These observations have indicated a mean clinical taper of 17° to 30° and an initial pressure of 6 kg typically reducing to 3 kg.

The order of retention of the various cements has been found to be composites > glass-ionomers/polycarboxylates > zinc phosphate > EBA cement. Prior use of eugeno1-based temporary cements appears to have no adverse effect, except possibly in the case of resin-based composites in conjunction with a volatile cleaning/drying agent.

These studies indicate that the effect of taper may be more complex that the literature suggests. In contrast to the accepted view of a monotonic relationship between retention and taper, the current study indicates that for most cements there may in fact be an optimum taper in the range 7° to 15°. The reason for this is unclear.

Recementation appears to have no adverse effect on retention. A separate clinical survival study ranked the cements in the order glass-ionomer/polycarboxylate > zinc phosphate > EBA, in full agreement with the in-vitro data.